Case Study: Pengaruh Keretakan Shaft Kopling Pompa Kargo Terhadap Kinerja Pompa Kargo Di SPOB Sea World One - Khaeroman, Khaeroman; Herdawan, Deri; Zaghlul Nafis, Ragil (PPPM Polimarin, 2023)
This article discusses the effect of a cracked clutch shaft on the performance of the gear pump type cargo pump at SPOB Sea World One. Damage was found to the clutch shaft which was indicated by a decrease in the pump flow rate on the ship during bunker service. The aim of this research is to determine the factors that cause clutch shaft cracks, as well as determine the impact of these cracks, and the handling efforts carried out on the clutch shaft. The method used in this research is a qualitative method which produces descriptive data in the form of written explanations. Data collection takes the form of an approach to the research object through direct observation and interviews as well as taking data from the ship. Based on the observations, it was concluded that the impact of the shaft cracking caused noise due to a gap and a drop in pump pressure. And it was found that the factor causing the shaft crack was the lack of implementation of a planned maintenance system on board the ship for the cargo pump, causing the pump to experience over running hours. Turning was carried out as an effort to handle the clutch shaft with an original diameter of 12 cm.